Capital structure and internationalization: The case of Portuguese industrial SMEs. - Pacheco, Luís Miguel (2016)
The central objective of this paper is to empirically examine the relationship between the capital structure of Portuguese small and medium enterprises (SMEs) and their export performance. We focus our study in the Portuguese industrial firms due to their importance for the Portuguese economy and role played in the country’s economic recovery amid the recessionary environment of the last decade. Though many empirical papers studied the determinant factors of capital structure, the interaction between export performance and capital structure has been much less studied. We intend to fill that gap, particularly for the case of Portugal and focusing on SMEs, where agency and asymmetric information problems could impact more on export performance, and not on large and listed corporations. Using panel data methodology, considering a sample of 3.164 firms and the period from 2011 to 2014, the paper extends the literature since analyzes the impact of the presence in foreign markets on short and long-term indebtedness. Distinguishing between different sectors of activity, the results suggest that profitability, asset tangibility, size, liquidity and presence in foreign markets are key factors affecting the capital structure of industrial SMEs. Albeit not validating the “upstream-downstream” hypothesis, we highlight the possible role played by agency costs and information asymmetries over debt during the internationalization process.